Structure and bonding in WCn (n = 2–5) clusters (2016)
Stochastic explorations of the configurational spaces for WC n (n = 2–5) clusters lead to densely populated spin states at each molecularity. We found 8, 16, 42, and 68 well-defined minima for n = 2, 3, 4, 5, respectively, in spin states ranging from singlets to quintuplets. The lowest energy isomers are triplets in all cases, except for n = 2 where there is competition between a quintuplet and a triplet state for the global minimum. The transition from planar to 3D structural preferences occurs between n = 4 and n = 5. For the global minima, the structures may be considered as the result of the interaction between two fragments: a tungsten cation and a covalently bonded anionic carbon chain. We found that spin–orbit (SO) effects reduce energy differences among isomers. Likewise, SO effects diminish as a function of the carbon content in the clusters to the point that for n = 5 they become negligible.